A Critical Exposition of the Philosophy of Leibniz - Russell, Bertrand 1872-1970 (London Allen & Unwin, 1975)
The writings of German mathematician and philosopher Gotffried Wilhelm Leibniz (1646-1716) have had an incalculable impact on modern science and technology, from physics and computers to law and psychology. But not everyone is a fervent fan. At the turn of the 20th century, the great British thinker Bertrand Russell uncovered what he believed was the hypocritical secret to Leibniz's philosophy: a hidden devotion to a logic he did not reveal in his writings. Here, Russell explores Leibniz's work from this perspective, examining the premises of Leibniz's work, the questions raised by his arguments, the validity of Leibniz's proofs, problems with his "philosophy of matter," and much more. First published in 1900, this is a replica of the 1937 second edition, and is complete with the original, extensive appendix of relevant extracts from Leibniz's work, essential for understanding Russell's critique.
This (2nd) edition was originally published in 1937, with the first edition published in 1900
With an Appendix of Leading Passages
Keywords: Leibniz, Gottfried Wilhelm -- 1646-1716; 17th Century (1601-1700); 18th Century (1701-1800); 19th Century (1801-1900); Philosophy; Germany